2010
DOI: 10.1111/j.1365-294x.2010.04805.x
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive paternity assignment: genotype, spatial location and social status in song sparrows, Melospiza Melodia

Abstract: Comprehensive, accurate paternity assignment is critical to answering numerous questions in evolutionary ecology. Yet, most studies of species with extra-pair paternity (EPP) fail to assign sires to all offspring. Common limitations include incomplete and biased sampling of offspring and males, particularly with respect to male location and social status, potentially biasing estimated patterns of paternity. Studies that achieve comprehensive sampling and paternity assignment are therefore required. Accordingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
220
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 86 publications
(224 citation statements)
references
References 60 publications
3
220
0
1
Order By: Relevance
“…From 1993 onwards, blood samples from the complete adult population allowed us to assign offspring to their genetic parents with high statistical confidence [23]. These analyses showed that 28 per cent of offspring were sired by an extra-pair male, while all mothers were correctly assigned by behaviour [23]. Based on this, we reconstructed the pedigree for the complete population, going back to the beginning of the study in 1975 [21,22].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…From 1993 onwards, blood samples from the complete adult population allowed us to assign offspring to their genetic parents with high statistical confidence [23]. These analyses showed that 28 per cent of offspring were sired by an extra-pair male, while all mothers were correctly assigned by behaviour [23]. Based on this, we reconstructed the pedigree for the complete population, going back to the beginning of the study in 1975 [21,22].…”
Section: Methodsmentioning
confidence: 99%
“…Circa 24 days post-hatching, when offspring begin foraging independently, territories are searched for offspring that have survived until independence from parental care. During 1993-2006, blood samples were collected from virtually all chicks that survived to ca 6 days post-hatch [23]. In 2004, nestlings were individually marked and a blood sample was taken when they were 1 day old to estimate the mortality rate between hatching and day 6.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, blood sampling of all individuals at approximately 6 days after hatching since 1993 allows correcting the pedigree for extra-pair paternities and determining the sex [37][38][39][40][41]. F was calculated using the R package pedigreemm [42] for individuals with at least two (and a mean of eight) genetically verified ancestral generations plus earlier genetically not verified generations.…”
Section: Materials and Methods (A) Inbreeding Coefficientsmentioning
confidence: 99%
“…Siring young outside a social pair bond has the ability to enhance productivity within a single breeding season and is an important component of male fitness (Griffith et al 2002, Kaiser et al 2015, but males within a population can differ considerably in their fitness gains from EPP (Sardell et al 2010;Reid et al 2014a;Kaiser et al 2015).…”
mentioning
confidence: 99%